Taboos in Dentistry: A Review - Gupta, Ankita; Vishwakarma, Manoj (Journal of Orofacial Research, 2023)
Lack of knowledge and awareness of people on oral heath gave rise to innumerable social misbeliefs in certain communities. In today's world, it is important for every dentist to have knowledge of the trending myths and taboos in dentistry to provide quality dental care to the patients. This short review of literature discusses the various social misconceptions and commonly encountered taboos in dentistry and the reasons for such misbeliefs.